Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Karyawan di Bagian Warehouse PT. PLN UP2D Wilayah Kabupaten Tangerang - Adita, Kristya; H, Herayati; Windasari, Vicky (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the influence of leadership style and work environment on employee performance in the Warehouse Division of PT. PLN UP2D Tangerang Regency Area. Employee performance is a crucial factor for the sustainability and success of an organization. This research employs a quantitative approach by distributing questionnaires to 45 employees during the period of March 5 to June 5, 2025. The data were analyzed using SPSS version 27, through validity and reliability tests, classical assumption tests, and multiple linear regression analysis to examine both partial and simultaneous influences between variables. The results show that both leadership style and work environment have a significant effect, both partially and simultaneously, on employee performance, with a contribution of 57.2%. Effective leadership and a conducive work environment are proven to enhance productivity. These findings provide recommendations for management to develop a more participative leadership style and to create a supportive work environment in order to optimize employee performance. This research may also serve as a foundation for future studies by adding other variables such as motivation, compensation, or organizational culture.